2013
DOI: 10.3344/kjp.2013.26.2.142
|View full text |Cite
|
Sign up to set email alerts
|

The Survey about the Degree of Damage of Radiation-Protective Shields in Operation Room

Abstract: BackgroundMedical doctors who perform C-arm fluoroscopy-guided procedures are exposed to X-ray radiation. Therefore, radiation-protective shields are recommended to protect these doctors from radiation. For the past several years, these protective shields have sometimes been used without regular inspection. The aim of this study was to investigate the degree of damage to radiation-protective shields in the operating room.MethodsThis study investigated 98 radiation-protective shields in the operation rooms of K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 18 publications
2
21
0
Order By: Relevance
“…Visual and tactile tests can be performed; in case of doubt, a fluoroscopic image can be taken to find uniformity or holes [ 34 ]. A survey on the degree of damage of lead aprons used during pain management in a general hospital operating room showed that the most common site of damage was the waist of the apron (51%), followed by the lower part of the apron (33%) [ 44 ]. An apron should always be handled carefully and kept hanging when not in use.…”
Section: Main Bodymentioning
confidence: 99%
“…Visual and tactile tests can be performed; in case of doubt, a fluoroscopic image can be taken to find uniformity or holes [ 34 ]. A survey on the degree of damage of lead aprons used during pain management in a general hospital operating room showed that the most common site of damage was the waist of the apron (51%), followed by the lower part of the apron (33%) [ 44 ]. An apron should always be handled carefully and kept hanging when not in use.…”
Section: Main Bodymentioning
confidence: 99%
“…Many surveys have shown a wide distribution of doses for patients' requiring the same type of radiographic examination (Kim et al, 2012). Skin diseases, thyroid cancer, brain tumors, and cataracts are several examples of the adverse effects of ionizing radiation on the human body (Ryu et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation protective garments could crack or tear over time, and the ability to shield radiation could be reduced. Therefore, all garments should be checked regularly using fluoroscopy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many ways to reduce the radiation exposure have been used [ 5 6 7 8 9 ]. And it implemented an education related to radiation safety.…”
Section: Introductionmentioning
confidence: 99%